(untitled) (Research, Society and Development, 2022)
Heart failure (HF) is considered a serious public health problem whose high prevalence is associated with population aging and improvements in treatment. This study aimed to evaluate the impact of an educational strategy on quality of life and adherence to outpatient treatment of patients with chronic heart failure. This is a randomized clinical study, divided into intervention (IG) and control (CG) groups by means of simple random sampling. All data were analyzed using STATA 14.0 and the significance level of p<0.05. The study was approved by the Research Ethics Committee. Based on the results, the comparison between the groups after the educational intervention showed statistical significance only in the assessment of quality of life using the WHOQOL-BREF questionnaire, in the psychological and environmental dimensions. However, no statistical differences were reported in treatment adherence scores between the groups after the intervention. The quality of life (QoL) rating by the Minnesota Living With Heart Failure Questionnaire (MLHFQ) after 12 months of intervention, that patients classified with good QoL increased from 33.3% to 57.41%, with moderate QoL increased from 31 .48% to 38.89% and with poor QOL there was a reduction of approximately 90%.